AN EVALUATION OF ACCESSIBILITY OF LOW-INCOME EARNERS TO HOUSING FINANCE IN NIGERIA - D, Adedeji Y. M.; Olotuah, Abiodun O. (European Scientific Journal, ESJ, 2012)
In Nigeria housing provision is fraught with a plethora of problems especially for low-income earners who incidentally constitute the majority of the population. Fundamental to this is the lack of access to housing finance by this segment of the society. In view of its enormous cost, housing is the item of the highest expenditure of every household and it can rarely be purchased directly from one.s earnings. Access to housing finance is thus imperative in the acquisition of housing, but this has always eluded low-income earners a great deal. This paper examines housing problems and needs of low-income earners, activities of private developers in housing provision in Nigeria, housing finance system and activities of cooperative societies in housing delivery. Survey research was conducted at The Federal University of Technology, Akure in the year 2009. Three hundred and fifty (350) questionnaires were administered out of which two hundred and ninety-seven (297) were retrieved for analysis. Results obtained show that the level of accessibility of low-income earners to housing finance in Nigeria is still very low despite the intermediation of private developers and cooperative societies in sourcing housing finance.